FAKTOR-FAKTOR YANG MEMPENGARUHI PENGAMBILAN KEPUTUSAN - Susanto, Teguh Trianung Djoko; Haryani, Tri; Farashati, Alfiya; Theoline, Easyah (Jurnal Manajemen Pendidikan, 2025)
This study aims to identify and analyze the main factors that influence the effectiveness of decision-making in educational organizations in Indonesia, especially in the context of digital transformation and post-pandemic policy dynamics. This study also aims to develop an integrative and contextual conceptual model to support ethical and data-driven decision-making. This study uses a Systematic Literature Review (SLR) approach following the PRISMA protocol. The literature reviewed was taken from the Scopus, ERIC, and Google Scholar databases with a publication year range of 2019–2024. Of the 123 initial publications, 45 articles that met the inclusion criteria were analyzed using thematic coding techniques to identify patterns and relationships between factors. Thematic analysis resulted in four main interacting factors: (1) individual factors (adaptive competence, personal values), (2) organizational structure (bureaucracy, work culture), (3) external pressures (policies, technology), and (4) values ​​and ethics. The interaction of these four factors forms four reinforcing loops that explain 72% of the variation in the effectiveness of decision-making in educational organizations. This study offers a new conceptual model called Ethical Data-Driven Decision Making (EDDM) that integrates data-driven rationality with ethical values ​​in decision making. This model is relevant in responding to the complexity of modern education governance that demands adaptive, accountable, and integrity-based decisions.